PENGARUH LATIHAN KOTAK TELEPON TERHADAP KETERAMPILAN MENGGIRING BOLA PADA PEMAIN SEPAKBOLA SSB PERSUBATIM ROKAN HULU - Fajri, Nurul Fajri Nurul; Wijayanti, Ni Putu Nita Wijayanti Nita; ', Slamet Slamet (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research was conducted from the researcher’s observation in the field on football players in SSB Surbatim Rokan Hulu. There was frequent weakness on the players in doing exercise or in match. It was caused by lack of using methods in dribbling exercise from the coach. The research was conducted to know weather there was the effect of phone box training in dribbling ability on football players in SSB Persubatim Rokan Hulu. In this research the populations were 24 players. The sample used by total technique sampling, so the participants were 24 players. The data were gotten from dribbling test. The result was gotten from pre-test and was analyzed with t-test. Based on hypothesis showed that Ttest was 2.883 and ttable was 1.711. It means that Ha was refused on alpha (α)0,05. It could be concluded that there was the effect of phone box training in dribbling ability on football Players in SSB Persubatim Rokan Hulu.Keywords: Phone Box, Dribbling